Using an Aqueous Suspension of Duddingtonia flagrans Chlamydospores and a Hexane Extract of Artemisia cina as Sustainable Methods to Reduce the Fecal Egg Count and Larvae of Haemonchus contortus in the Feces of Periparturient Ewes - Héctor Alejandro de la Crúz-Crúz; Rosa Isabel Higuera-Piedrahita; Alejandro Zamilpa; Yazmín Alcalá-Canto; Ana Yuridia Ocampo-Gutiérrez; Luis David Arango-de la Pava; María Eugenia López-Arellano; Daniel Hernandez-Patlan; Jorge Alfredo Cuéllar-Ordaz; Pedro Mendoza-de Gives (Pathogens)
This study evaluated the effectiveness of Duddingtonia flagrans chlamydospores and an Artemisia cina hexane extract in reducing Haemonchus contortus fecal egg counts and larvae in periparturient ewes. This study involved five groups of four ewes: a control group, an ivermectin group, an A. cina oral extract group, a D. flagrans group, and a combined treatment group. Treatments began two weeks before delivery, with ivermectin administered 15 days before delivery. Fecal samples were collected every fifteen days to estimate parasite egg counts per gram of feces (EPG) and assess larvae reductions. The results showed very low EPG values for ivermectin and D. flagrans treatments (175 and 150, respectively). The control and combined treatment groups had EPG values rise to 3000 and 4100 by day 15. The EPG values for the A. cina group reached 850 and 533 in later samplings. Throughout the study, the D. flagrans and A. cina groups maintained low EPG values, with the highest recorded values being 50 and 0, respectively. All treatments significantly reduced the larvae in the fecal cultures: D. flagrans (97.4% reduction), ivermectin (91.4%), Artemisia cina (89.9%), and the combined treatment (84.3%).